2020
DOI: 10.3151/jact.18.456
|View full text |Cite
|
Sign up to set email alerts
|

Thermoporometry and Proton NMR Measurement on Cement Paste Equilibrated at Different Relative Humidities

Abstract: In this study, thermoporometry by differential scanning calorimetry and proton NMR measurements of hardened cement paste equilibrated under different humidity conditions were carried out, and the results of both measurements were compared. The results reveal that thermoporometry by low temperature DSC measurement cannot detect the water present in samples equilibrated at low relative humidity. On the other hand, it is possible to detect a signal at low relative humidity by proton NMR measurement. It is clarifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Bager and Sellevold [40] reported that no ice was formed in hardened cement paste equilibrated at RH of 33 % and 11 %. No exothermic peak was detected in white cement paste at 33 % RH [41] as well. Fig.…”
Section: Thermoporometry Analysis Of Lt-dscmentioning
confidence: 88%
“…Bager and Sellevold [40] reported that no ice was formed in hardened cement paste equilibrated at RH of 33 % and 11 %. No exothermic peak was detected in white cement paste at 33 % RH [41] as well. Fig.…”
Section: Thermoporometry Analysis Of Lt-dscmentioning
confidence: 88%
“…In some previous studies, measurements were performed by changing τ [38,39], but preliminary tests confirmed that the results obtained using a single τ did not differ. It has also been reported that the presence of aluminum affects the signal, but the measurements herein were performed to observe the qualitative effect [40].…”
Section: Proton Nmr Measurementmentioning
confidence: 91%